Peningkatan Mutu Madrasah melalui Penguatan Partisipasi Masyarakat - K.A. Rahman (Jurnal Pendidikan Islam, 2012)
Quality in the context of education is a process to do it right the first time andmake continuous improvements from setting the vision, mission, purpose, operation, monitoring, and evaluation of substances intended for meaningful education, that begins from input-process and out-put, up to the level of outcome. In the world of education, including the madrasa, community satisfaction will be realized when the madrasa’s’ quality has a continuous benefits for society.